Real world evidence for public health decision-making on vaccination policies: perspectives from an expert roundtable - Chiara de Waure; Barbara C. Gärtner; Pier Luigi Lopalco; Joan Puig-Barbera; Jonathan S. Nguyen- (Taylor & Francis Group, 2024)
ABSTRACTIntroduction Influenza causes significant morbidity and mortality, but influenza vaccine uptake remains below most countries' targets. Vaccine policy recommendations vary, as do procedures for reviewing and appraising the evidence.Areas Covered During a series of roundtable discussions, we reviewed procedures and methodologies used by health ministries in four European countries to inform vaccine recommendations. We review the type of evidence currently recommended by each health ministry and the range of approaches toward considering randomized controlled trials (RCTs) and real-world evidence (RWE) studies when setting influenza vaccine recommendations.Expert Opinion Influenza vaccine recommendations should be based on data from both RCTs and RWE studies of efficacy, effectiveness, and safety. Such data should be considered alongside health-economic, cost-effectiveness, and budgetary factors. Although RCT data are more robust and less prone to bias, well-designed RWE studies permit timely evaluation of vaccine benefits, effectiveness comparisons over multiple seasons in large populations, and detection of rare adverse events, under real-world conditions. Given the variability of vaccine effectiveness due to influenza virus mutations and increasing diversification of influenza vaccines, we argue that consideration of both RWE and RCT evidence is the best approach to more nuanced and timely updates of influenza vaccine recommendations.